Studi Klimograf Perubahan Cuaca dan Bangkitan Malaria di Kabupaten Banjarnegara - Raharjo, Mursid (Jurnal Kesehatan Lingkungan Indonesia, 2003)
ABSTRACT Background : Malaria in Banjarnegara district is inequitable distribution. The fluctuate of meteorology factors was a dominant factor of the vector densities. This is very important object  especially to evaluate the correlation between the  climograph of meteorology data  and malaria incidence. The climograph was the important instrument to predicted the re-emerging of malaria. Methods : Based on the malaria incidence and the meteorological data in ten years, the phenomena of climate change  was analyzed. Correlation between malaria incidence and meteorology data analyses  by  the Pearson Product Moment. Climograph was composed by the  average of meteorology data as long as ten years period. Average of yearly meteorology climograph was composed by the yearly meteorology data. The overlay of the two climograph  conclude relationship between malaria case incidence and fluctuate of meteorology. Results :  The results of the research showed coefficient of  correlation rainfall to malaria incidence –0,75, correlation of air temperature to malaria incidence –0,6875, and correlation  of  air humidity  to  malaria  incidence –0,6407. If the annual  climograph as same as range with the average of the ten years climograph, incidence of malaria was low (1995, API 0,02).   If the annual  climograph different  with the average of the ten years climograph in which the incidence of malaria was high (2001, API 15,53). Key : Malaria incidence, Climograph study, Re-emerging disease